Pengaruh Komposisi Katalis H-Zeolit Dan Kecepatan Pengadukan Pada Sintesa Plastisizer Butil Oleat - Rinanda, Wahyu Okta; HS, Irdoni; Nirwana, Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Oil palm commodity has a strategic role in the national economy. In the development of the palm oil industry, the necessary diversification of oil palm products needed by using the esterification reaction. One of the products of the oil palm which on development now is a fatty acid alkyl esters. Products that include the type of fatty acid alkyl ester is plasticizer. In this study, the plasticizer is synthesized by esterification of oleic acid and butanol, using activated natural zeolite catalysts. This research aims to study the influence of H-Zeolite catalyst composition and stirring speed on synthesis plasticizer butyl oleate, and determining the characteristics of the plasticizer butyl oleate which generated through analysis of test products. The process is using the variation of H-Zeolite catalyst composition (12.5%, 15%, 17.5%) based on oleic acid and stirring speed (175 rpm, 200 rpm, 225 rpm), with a fixed variable, the reaction temperature of 1100 C, the process time is 6 hours and the reaction molar ratio of 1: 9. From the analysis of the results showed that the esterification of H-Zeolite catalyst composition and stirring speed affects the conversion of the resulting products. The best operating conditions obtained in this study is the H-Zeolite catalyst composition of 17.5% and a stirring speed of 200 rpm which produces a reaction conversion of 74.50%. Characteristics plasticizer generated in this study is consistent with the characteristics of commercial plasticizers which Viscosity (200 C) 8.62 to 9.07 mPa.s and Specific Gravity (200 C) from 0.886 to 0.901.Keywords: Butyl Oleate, Esterification, H-Zeolite and Plasticizer